ChemInform Abstract: Multitargeted Drug Development: Discovery and Profiling of Dihydroxy Substituted 1‐Aza‐9‐oxafluorenes as Lead Compounds Targeting Alzheimer Disease Relevant Kinases. Issue 14 (20th March 2013) - Tell, Volkmar; Holzer, Max; Herrmann, Lydia; Mahmoud, Kazem Ahmed; Schaechtele, Christoph; Totzke, Frank; Hilgeroth, Andreas
Abstract Two new nanomolar active CDK1, CDK5/p25 and GSK‐3β inhibitors of the 3, 6‐dihydroxy‐1‐aza‐9‐oxafluorene type (IV) are discovered.